Comparison the effect of carboxymethyle cellulose films containing Thymus vulgaris and Zataria multiflura on shelf life of chicken meat - Narjes Janatiha; Saeedeh Shojaee Aliabadi; Maryam Moslehi Shad (Islamic Azad University, 2017)
Poultry meat is a kind of perishable food. The growth of pathogenic microorganisms may occur in chicken meat during storage in the refrigerator. Microbial growth causes a serious hazard to the safety of the food consumer. The aim of this study was to compare antimicrobial properties of Thymus vulgaris (TEO) and Zataria multiflora essential oil (ZEO) and the effect of carboxymethyl cellulose (CMC) films containing essential oil on shelf life of chicken meat during 9 days at 4° C. Essential oil was extracted by distillation. At first, antimicrobial activities of CMC film containing essential oil and control films were analyzed by disc diffusion assay. After that, three treatments of chicken fillets including untreated-control (C), coating carboxymetyl cellulose (CMC), and CMC with 2.4% Zataria multiflora essential oil (CMC-Z) were prepared. The microbial shelf life of treatment were determined in 3 days interval at 4 ̊° C. The results showed that antimicrobial properties of Thymus vulgaris and Zataria multiflura essential oil, ZEO containing film had efficient inhibitory effect compared to TEO, thus film incorporated with ZEO was selected for shelf life studies. Also the results revealed that total viable count (TVC) population of fillets increased during shelf life and exceeded 6.81 log cfu g -1 for CMC sample on day 8. For CMC-Z treatments, this deadline was achieved after 9 days. Coating chicken meat sample with CMC film could decrease TVC population compared to the control sample (p<0.05). The results showed that the use of ZEO in chicken meat as antimicrobial compound caused a delay in microbial putrefaction process.